Peningkatan Margin Kontribusi dan Nilai Tambah Aneka Produk Olahan Rumput Laut di Desa Bungin Permai, Konawe Selatan, Sulawesi Tenggara - Ine Fausayana; . Rosmawaty; . Akhyar (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This Community Partnership Program (CPP) activity was implemented in the seaweed farming business unit in Bungin Permai Village, Tinanggea District, South Konawe District, Southeast Sulawesi. The Community Partnership Program (PKM) activity is carried out in the seaweed farmer's business unit UMKM Kumbang Laut and Sinar Laut in Bungin Permai Village, Tinanggea District, South Konawe Regency. Each group consists of 10 people who carry out various seaweed processing businesses. The problems of UMKM is the limited introduction of technology and business management capabilities so that it has an impact on the low contribution margin and added value. This activity aims to increase the contribution margin and the added value of various processed seaweed products. The results showed that the production value seaweed ice cream and seaweed banana nuggets was IDR 80,000 each. Comparison of contribution margins was IDR 40,340 and IDR 37,550. Added value after processing amounted to 37,740 and 31,050. So the added value produced per 1 kg of dried seaweed for each product is IDR 188,700 and IDR 155,250.